2006
DOI: 10.3748/wjg.v12.i48.7792
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific health-related quality of life and its determinants in liver cirrhosis patients in Lithuania

Abstract: QOL was significantly impaired in all CLDQ domains in liver cirrhosis patients. Increase in severity of disease was the major factor associated with poorer QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
34
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 28 publications
9
34
1
5
Order By: Relevance
“…The overall CLDQ score as well as the domain sub scores showed an inverse relationship with the disease severity. Similar pattern of association between Child Pugh Score and CLDQ has been demonstrated by other studies also 3,11,16,[23][24][25] . The post-hoc analysis revealed that the average and the sub scores of patients with Child C were significantly low than patients with both Child A and B, however most of the studies using CLDQ have not been able to differentiate between Child C and B 3,6,26 .…”
supporting
confidence: 86%
“…The overall CLDQ score as well as the domain sub scores showed an inverse relationship with the disease severity. Similar pattern of association between Child Pugh Score and CLDQ has been demonstrated by other studies also 3,11,16,[23][24][25] . The post-hoc analysis revealed that the average and the sub scores of patients with Child C were significantly low than patients with both Child A and B, however most of the studies using CLDQ have not been able to differentiate between Child C and B 3,6,26 .…”
supporting
confidence: 86%
“…The original instrument was tested within a group of 133 patients and showed appropriate reliability and validity [3]. Since then, several studies have confirmed the ability of the CLDQ to discriminate between different stages of disease severity according to Child class [4][5][6][7][8][9][10]. Another study found that the CLDQ could discern between patients with and without comorbid diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the CLDQ has proven to be responsive after liver transplantation [9,12] as well as after application of self-care and educational programs [13,14]. Between 2004 and 2006, a Thai [8], an Italian [11], a Spanish [9], and a Lithuanian [10] adaptation of the CLDQ were published. A German adaptation of the CLDQ was developed by Häuser et al in 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that biochemical markers, socio-demographic and psychosocial factors did affect HRQOL in patients with CLD but it has not been fully examined in Chinese CHB patients Bianchi et al, 2003;Hauser, Schnur, Steder-Neukamm, Muthny, & Grandt, 2004;Hussain et al, 2001;Marchesini et al, 2001;Sobhonslidsuk et al, 2006;Sumskiene, Sumskas, Petrauskas, & Kupcinskas, 2006;Younossi et al, 2001;Younossi et al, 2000). Disease severity, as measured by Child-Pugh scores or stage of CHB illness (asymptomatic, impaired liver function, cirrhosis and HCC), was one of the commonest factors that had a negative relationship with HRQOL Marchesini et al, 2001;Sobhonslidsuk et al, 2006;Sumskiene et al, 2006;Younossi et al, 2001;Younossi et al, 2000). However, some studies did not find any significant effect between HRQOL and disease severity (Hauser, Holtmann, & Grandt, 2004;Hauser, Zimmer, Schiedermaier, & Grandt, 2004).…”
Section: Wwwintechopencommentioning
confidence: 99%